Análisis del perfil del turista en el distrito de Iquitos año 2017 - Marin Vargas, Veronica del Carmen (2019)
The objective of this research was to analyze the characteristics of the tourist profile in the district of Iquitos, in the year 2017. The simple descriptive design was applied, based on a population of 2500 national tourists. Also, it was obtained as a result that, tourists present a sociodemographic profile, which is characterized by a male population between 25 and 34 years old, mostly coming from the city of Lima and with a university degree, concluding that, the city of Iquitos presents many attractive things to the national and foreign tourist.